Enhancing the efficiency of sodium borohydride hydrolysis with a novel CoB-Triton catalyst - Kaya, Cenk; Ozdemir, Julide Hazal; Elcicek, Huseyin; Ozdemir, Oguz Kaan; Kokkulunk, Gorkem; Unlugencoglu, Kaan (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Hydrogen is increasingly recognized as the most significant alternative solution for reducing global greenhouse gas emissions in maritime transportation. In particular, solidstate sodium borohydride (NaBH4) with its high hydrogen storage density stands out as the preferred choice due to its higher efficiency and improved safety. In present study, a surfactant-stabilized CoB catalyst was used in order to improve the hydrolysis performance of NaBH4. For this reason, the effects of Triton X-100, used as a surfactant in different quantities, on the hydrogen generation rate were tested. To characterize the prepared samples, several analytical techniques were employed, including field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FT-IR), Mastersizer analysis, X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET) analysis. According to findings, 40.2% faster hydrogen generation rate is obtained with CoB-Triton 150 contrary to CoB catalyst. The optimum concentrations are found as 5% NaOH and 5% NaBH4 and activation energy is 44.21 kj/mol for developed CoB-Triton 150 catalyst. Last of all, fuel cell performances show that the produced hydrogen from hydrolysis reaction through CoB-Triton 150 catalyst has nearly same fuel cell performance compared to industrial pure hydrogen. Consequently, Triton X-100 is a good candidate to improve the hydrolysis performance of NaBH4 and needs further research. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Surfactant; Triton X-100; Cobalt boride catalyst; Hydrolysis of NaBH4; CE-B NANOPARTICLES; HYDROGEN GENERATION; HIGH-PERFORMANCE; NABH4; CARBON; FUEL; ENERGY; NI; OPTIMIZATION; STORAGE; Chemistry; Electrochemistry; Energy & Fuels